2009
DOI: 10.1063/1.3275853
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of dynamic wetting far from equilibrium

Abstract: In this paper we present simulations of dynamic wetting far from equilibrium based on phase field theory. In direct simulations of recent experiments ͓J. C. Bird, S. Mandre, and H. A. Stone, Phys. Rev. Lett. 100, 234501 ͑2008͔͒, we show that in order to correctly capture the dynamics of rapid wetting, it is crucial to account for nonequilibrium at the contact line, where the gas, liquid, and solid meet. A term in the boundary condition at the solid surface that naturally arises in the phase field theory is int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
103
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 12 publications
3
103
0
3
Order By: Relevance
“…A non-monotonicity in µ f is observed for pure water for the SiO 2 and silane coating, the same dependency was reported in [14] when comparing with similar experiments [2]. We can at the present time not explain this non-monotonicity for pure water.…”
supporting
confidence: 35%
See 3 more Smart Citations
“…A non-monotonicity in µ f is observed for pure water for the SiO 2 and silane coating, the same dependency was reported in [14] when comparing with similar experiments [2]. We can at the present time not explain this non-monotonicity for pure water.…”
supporting
confidence: 35%
“…If accounting for the effects of convection of the concentration, that would equal the flux due to gradients of the chemical potential, the Cahn-Hilliard equation is recovered, which along with the Navier Stokes equations forms a theoretical basis for modeling of wetting [14] with a no-slip on the wall.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Qian et al 15 included such relaxation in their computation of the Couette flow but did not examine its effect. The simulation of Carlson et al 16 indicated that wall relaxation tends to inhibit the motion of the contact line and reduce the speed of drop spreading. But the mechanism for this is unclear.…”
Section: Introductionmentioning
confidence: 99%